Getting started with Hazelcast : get acquainted with the highly scalable data grid, Hazelcast, and learn how to bring its powerful in-memory features into your application /: get acquainted with the highly scalable data grid, Hazelcast, and learn how to bring its powerful in-memory features into your application. (2015) - Johns, Mat
No abstract available